Detrital Zircon Age Constraints on the Evolution of Paleo‐Tethys in NE Iran: Implications for Subduction and Collision Tectonics. Issue 8 (12th August 2021) - Chu, Yang; Wan, Bo; Allen, Mark B.; Chen, Ling; Lin, Wei; Talebian, Morteza; Xin, Guangyao
Abstract: The timings of the onset of oceanic spreading, subduction and collision are crucial in plate reconstructions, but not always straightforward to resolve. The Paleo‐Tethys evolution dominated the Paleozoic‐Early Mesozoic tectonics of West Asia, but the timeline of events is still poorly constrained. We present new detrital zircon ages from the Binalud Mountains of NE Iran, in order to determine the timing of tectonic events in the region, and the wider implications for regional tectonics, paleogeography and climate change. Consistent age patterns in Paleozoic clastic rocks show a dominant provenance from the Neoproterozoic basement of northern Gondwana. We interpret this as deposition on a long‐lasting passive continental margin after the initial spreading of the Paleo‐Tethys Ocean. Central Iran‐Eurasia collision caused coarse clastic deposition of the Mashhad Phyllite in a peripheral foreland basin on the Paleozoic sequence of the northern Central Iran Block. The Mashhad Phyllite yields age clusters at 450–250 Ma and 1, 900–1, 800 Ma, with a clear provenance from a long‐lived continental arc at the active Eurasian margin since the latest Ordovician. Analysis of the age spectra allows us to constrain the maximum depositional age of the Mashhad Phyllite as no later than 228 Ma. This age provides a tight constraint on the timing of initial collision between Central Iran and Eurasia, which also coincides with the Carnian Pluvial Event (CPE). Our new timing evidence of collision reinforces the previous speculation on the Paleo‐Tethys closure as a causal mechanism for the CPE. Key Points: Continuous Paleozoic arc magmatism developed in the South Turan Block, with intermittent peaks The onset of Central Iran‐Eurasia collision was no younger than 228 Ma, ending the passive margin sedimentation of Paleozoic Closure of Paleo‐Tethys was coincident with the Carnian Pluvial Event, and may have been a causal factor